Defect‐Rich Heterogeneous MoS2/NiS2 Nanosheets Electrocatalysts for Efficient Overall Water Splitting. Issue 14 (20th May 2019) - Lin, Jinghuang; Wang, Pengcheng; Wang, Haohan; Li, Chun; Si, Xiaoqing; Qi, Junlei; Cao, Jian; Zhong, Zhengxiang; Fei, Weidong; Feng, Jicai
Abstract: Designing and constructing bifunctional electrocatalysts is vital for water splitting. Particularly, the rational interface engineering can effectively modify the active sites and promote the electronic transfer, leading to the improved splitting efficiency. Herein, free‐standing and defect‐rich heterogeneous MoS2 /NiS2 nanosheets for overall water splitting are designed. The abundant heterogeneous interfaces in MoS2 /NiS2 can not only provide rich electroactive sites but also facilitate the electron transfer, which further cooperate synergistically toward electrocatalytic reactions. Consequently, the optimal MoS2 /NiS2 nanosheets show the enhanced electrocatalytic performances as bifunctional electrocatalysts for overall water splitting. This study may open up a new route for rationally constructing heterogeneous interfaces to maximize their electrochemical performances, which may help to accelerate the development of nonprecious electrocatalysts for overall water splitting. Abstract : A synthetic strategy is provided to rationally construct defect‐rich heterogeneous MoS2 /NiS2 nanosheets directly on carbon cloth and the influence of interface configuration on the electrocatalytic performances is investigated. The abundant heterogeneous interfaces in MoS2 /NiS2 can not only provide rich electroactive sites but also facilitate the electron transfer, which further cooperate synergistically toward electrocatalytic reactions.